Optimization Design of a Portable Hose Reel Using Integrated Approach - Samsudin, Abdul Rahim; Hambali, A; Marjom, Zolkarnain; Sivarao, Subramonian; Khairul, A A R (Universiti Teknikal Malaysia Melaka, 2010)
Development of a portable hose reel using integrated approach is addressed in this paper. Various design tools such as SolidWorks and Quality Function Deployment, (QFD) were intensively employed to improve the current hose reel design. To optimize the design, design problems and customer requirements were conducted by questionnaires and analyzed using house of quality (HOQ). Various conceptual designs of hose reel have been proposed and the most appropriate one is determined by implementing Pugh selection method. It is revealed that sketch concept 5 is the most appropriate design and further design development using Solidworks and final design is carried out at the detail stage. By implementing various design tools can lead the optimization of design during development of a product.